Pervaporation of ethanol-water using chitosan-clay composite membrane - Mohd Nawawi, Mohd Ghazali; Sadikin, Aziatul Niza; Tan, Gi Gi (Penerbit UTM Press, 2008)
The pervaporation performance for the separation of ethanol-water azeotrope mixture was assessed by chitosan-clay composite membranes. Composite hydrophilic chitosan membrane was prepared from commercially available chitosan powder. The chitosan powder was dissolved using dilute acetic acid to produce chitosan solution. The chitosan solution was blended with small amount of clay and casted on a porous support which prepared from polysulfone to produce composite membrane. The performance of the membrane for the pervaporation separation of ethanol-water mixtures with various concentrations was explored. The effects of feed temperature on the permeation flux and separation factor were also investigated. The membrane was tested for ethanol-water mixtures separation with different ethanol concentrations (10 wt%, 30 wt%, 50 wt%, 70 wt% and 90 wt%) at room temperature. The effects of feed temperature was studied using a feed solution containing 90 wt% ethanol; the feed temperature was varied from 30 Â°C to 70 Â°C at permeate pressure below 0.07 bar. The results showed chitosan-clay composite membrane performed better with low water content carried out at low temperature and permeate pressure. There was a trade-off between the permeation flux and the separation factor where the flux decreased while the separation factor increased with the increasing of ethanol concentration in the ethanol-water mixtures.